Improving Teacher Performance Through Education and Training - Rukhayati, Siti; Yanto, Heri; Masrukhi, Masrukhi; Suminar, Tri (Proceedings of International Conference on Science, Education, and Technology, 2024)
Teachers are the main factor that determines the success of students. The purpose of this study is first, to find out the problems of teachers of Private Aliyah Madrasah in Semarang Regency related to education and training, and the second solution is to overcome teacher problems related to education and training in teachers of Private Aliyah Madrasah in Semarang Regency. This research is qualitative research with a descriptive approach. The data collected is in the form of words or images from interviews, field notes and personal documents. The research was carried out at a Private Aliyah Madrasah in Semarang Regency. The stages of the research include making observations, determining key persons, informants with snowbolling techniques. The subjects of the study were the heads of madrasas and teachers in 11 Private Aliyah Madrasah in Semarang Regency. Data collection uses interviews, observations and documentation. Data analysis starts from data collection, data reduction, data presentation, and conclusion drawn. The results of the research, first , the problems of teachers of Private Aliyah Madrasah in Semarang Regency related to education and training are 1) teachers have not been able to participate in education and training, 2) teachers have not been able to fully implement the results of training because school facilities are not supportive, 3) teachers are busy with full teaching hours and administrative tasks at school, 4) teachers do not want to develop themselves by learning because they are busy with work or for health reasons 5) lack of intensive coaching and motivation from school leaders. Second, the solution to overcome the problems of teachers in Private Aliyah Madrasah Semarang Regency related to education and training is 1) the need for equal distribution of teachers to participate in education and training. 2) school infrastructure needs to be improved, especially internet and library facilities, 3) teachers are not burdened with many administrative tasks, 4) the need for teachers' awareness to develop themselves. 5) School leaders provide intensive coaching and motivation to teachers.